Implementation of oligonucleotide-gated supports for the electrochemical detection of Ochratoxin A. Issue 11 (2nd November 2017) - Muthamizh, Selvamani; Ribes, Àngela; Anusuyajanakiraman, Manokaran; Narayanan, Vengidusamy; Soto, Juan; Martínez-Máñez, Ramón; Aznar, Elena
Abstract: We report herein the design a hybrid material for the recognition of Ochratoxin A (OTA) by using an aptamer gated-material able to release electroactive species, which can be measured using differential pulse voltammetry. Mesoporous silica nanoparticles loaded with Methylene Blue and capped with an OTA aptamer were prepared and characterised. A highly selective and sensitive response due to the displacement of the capping aptamer in the presence of OTA and subsequent MB release was found in aqueous media. Finally, the possible use of the gated material for the detection of OTA in a real matrix was also explored. Abstract :